2015
DOI: 10.12740/pp/30455
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation as a method of chronotherapy in the treatment of depression

Abstract: Disturbances of circadian rhythms play an important role in the pathogenesis of affective illnesses, and their normalisation with methods of chronotherapy might become an important element of therapeutic treatment. Chronotherapy is based on a controlled exposure to environmental stimuli which affect biorhythms. One of the chronotherapeutic methods is sleep deprivation (SD). The article discusses the present status of SD in psychiatry, its methods and application in depression treatment. Presently the most reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…Use of SD has resulted in faster treatment response and increased BDNF levels [24]. One study found that in patients who achieved an antidepressant effect after SD, the expression of the circadian clock genes (e.g., RORA, DEC2, and PER1) increased, but in patients without such an effect, a significant decrease in the expression of these genes was found [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Use of SD has resulted in faster treatment response and increased BDNF levels [24]. One study found that in patients who achieved an antidepressant effect after SD, the expression of the circadian clock genes (e.g., RORA, DEC2, and PER1) increased, but in patients without such an effect, a significant decrease in the expression of these genes was found [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Vogel et al [101] described that the REMSD was also effective. Gillin [102], in 1983, pointed out that of a total of 852 patients who were TSD or REMSD for one or more nights, 493 (57.9%) were reported to have "improved", but it is recognized that this improvement in mood is transient and it is currently recommended that the TSD or REMSD be combined with sleep phase advance (SPA), pharmacotherapy, and sometimes also phototherapy [103].…”
Section: Sleep Deprivation In Humansmentioning
confidence: 99%
“…It was declared that SD affects positively in any kind of depressive disorders regardless of age. The mechanism of SD can be expressed as the monoaminergic neurotransmission increasing serotonin, noradrenaline and dopamine neurotransmission, alterations in the immune and endocrine systems and functional connectivity in the brain areas (Selvi et al, 2015, Dopierała & Rybakowski, 2015.…”
mentioning
confidence: 99%
“…Approximately 60% of the patients show clinical improvement the day immediately after the TSD night but after the recovery sleep 50±80% of SDresponders relapse (Pilkington, 2013). It is still not obvious how many hours of sleep deprivation are needed accurately antidepressant effect (Dopierała & Rybakowski, 2015). On the other hand, it is demonstrated that the antidepressant effect is connected to SD in the second half of the night (Dopierała & Rybakowski, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation